IMAGE ENCRYPTION AND DECRYPTION USING AES ALGORITHM - Patil, Sandip S (INTERANTIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2023)
Security concerns have taken front stage in the rapidly expanding digital exchange of data storage and transmission. Since the use of images is expanding quickly across a wide range of industries, it is crucial to safeguard sensitive image data from hackers. The need for image protection has become critical. It is now essential to secure someone's privacy. The preservation of data and personal information has been studied and developed using a variety of ways. Image encryption is used to shield sensitive data from unauthorised users. One of the most popular methods for keeping data concealed from unauthorised access is encryption. For picture encryption, the Advanced Encryption Standard (AES) is utilised, which leverages the key stream generator to improve image encryption performance. Keywords- ➢ AES:- Advanced Encryption Standard ➢ DES:- Data Encryption Standard